A BRIEF ANALYSIS OF DUBAI’S CREATIVE ECONOMY - Daminova , Madinaxon (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This thesis analyzes the development strategy of the creative economy in Dubai and its contribution to economic growth. In particular, it examines the targets set under the “Dubai Creative Economy Strategy,” including increasing the share of creative industries in GDP, expanding the number of creative firms, and boosting employment. The findings indicate that design and creative services, as well as audiovisual and interactive media, are leading sectors. Furthermore, the study highlights the importance of KPI-based policy management, institutional support, and cooperation with international organizations in fostering the creative economy.